Specific and sensitive detection of bovine coronavirus using CRISPR-Cas13a combined with RT-RAA technology - Liang, Zili; Luo, Ruxing; He, Qifu; Tang, Cheng; Zhang, Zhidong; Li, Yanmin; Guo, Zijing (Frontiers in Veterinary Science, 2025)
IntroductionBovine coronavirus (BCoV) is an important pathogen of enteric and respiratory disease in cattle, resulting in huge economic losses to the beef and dairy industries worldwide. A specific and sensitive detection assay for BCoV is critical to the early-stage disease prevention and control.MethodsWe established a specific, sensitive, and stable assay for BCoV nucleic acid detection based on CRISPR/Cas13a combined with reverse transcription recombinase-aided amplification (RT-RAA) technology. The specific primers for RT-RAA and CRISPR RNA (crRNA) were designed in the conserved region of the BCoV nucleocapsid (N) gene.ResultsThe detection limit of the RT-RAA CRISPR/Cas13a assays for BCoV detection was 1.72 copies/μl, and there were no cross-reactions with the other 10 common bovine enteric and respiratory disease-associated pathogens. The coefficient of variations (CVs) of within and between batches were less than 4.98 and 4.58%, respectively. The RT-RAA-CRISPR/Cas13a assays work well in clinical samples of cattle and yak, the BCoV positive rate of 84 clinical samples detected by RT-RAA-CRISPR/Cas13a assays was 58.3% (49/84), it was notably higher than that of RT-qPCR (2.4%, 2/84; p < 0.001). The 49 positive samples detected by RT-RAA-CRISPR/Cas13a assays were further confirmed as BCoV by Sanger sequencing.DiscussionA specific, sensitive, and stable assay based on RT-RAA-CRISPR/Cas13a assays for BCoV was developed, providing new technical support for the clinical detection and epidemiological monitoring of BCoV.